Inhibitory Anorectal Reflex in Acquired Megacolon is Rectal Volume Dependent in Manometric Evaluation - Enio C Oliveira (World Journal of Colorectal Surgery)
Background: The pathophysiology of acquired chagasic megacolon is based on the destruction of the enteric nervous system, leading to dysmotility, achalasia of the internal anal sphincter, and consequently constipation and colon dilation. This study reappraises the role of internal anal sphincter achalasia in such patients.